PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, LEVERAGE, KEPEMILIKAN INSTITUSIONAL, DEWAN KOMISARIS, DAN UMUR LISTING TERHADAP IMPLEMENTASI GOOD CORPORATE GOVERNANCE (SURVEI PADA PERUSAHAAN JASA SEKTOR PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BEI TAHUN 2014 – 2016) - Sari, Novita; Kristianto, Djoko; Puji Astuti, Dewi Saptantinah (Universitas Slamet Riyadi, 2019)
This research aim to analyze factors which affect the Implementation of Good Corporate Governmant in annual report of property and real estate companies listed in Indonesian Stock Exchange from 2014 to 2016. The factors tested in this research are Company Size, Profitability, Leverage, Institutional Ownership, Board of Commissioners, and Firm Listing Age as independent variables. The population in this study are property and real estate companies listed in Indonesian Stock Exchange from 2014 to 2016. The technique of sampling uses purposive sampling method and obtained 14 companies. This study using multiple regression analysis to tested factors which affect the Implementation of Good Corporate Government. The result showed that Institutional Ownership has effect on implementation of good corporate government. Meanwhile the other variables, Company Size, Profitability, Leverage, Board of Commissioners, And Firm Listing Age do not have effect on Implementation of Good Corporate Government. Further research is expected to increase the numbers of samples and not only focus on property and real estate companies as the object of research.